Market timing ability and volatility implied in investment newsletters' asset allocation recommendations - Graham, John R.; Harvey, Campbell R. (Journal of Financial Economics, 1996)
We analyze the advice contained in a sample of 237 investment newsletter strategies over 1980-1992. Each newsletter strategy recommends a mix of equity and cash. We find no evidence that letters systematically increase equity weights before market rises or decrease weights before market declines. While there is no information in the newsletter strategies about future market returns, we document that disagreement among the newsletters is correlated with future realized and implied volatility.